2022
DOI: 10.1177/10126902221110157
|View full text |Cite
|
Sign up to set email alerts
|

Tokyo 2020 Olympics sustainability: An elusive concept or reality?

Abstract: The Olympic Games continue to be a creator of adverse environmental impacts for host communities. Given the role that the Olympic Games play in sustainability due to their size, the number of people attending, new construction and infrastructure, and the extensive exposure by the media, this study investigated the Tokyo 2020 Games by evaluating the efficacy of their ecological sustainability efforts. Methods for this study were framed by the conceptual model of Müller et al. Specifically, the model is grounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In sum and regarding the guiding research question, it is now evident that despite initial aspirations for a more sustainable and inclusive city, the practical outcomes of hosting the Games did not adequately address the fundamental urban challenges and the needs of Rio's residents. Despite promising sustainable development, there was a significant disconnection between promises and achievements [33,93]. As emphasized by Wade [91], the Rio Games were largely marked by scandals and left the city starkly divided between rich and poor, much as it was with only a few cosmetic changes.…”
Section: Operational Insights From the Rio Gamesmentioning
confidence: 99%
See 3 more Smart Citations
“…In sum and regarding the guiding research question, it is now evident that despite initial aspirations for a more sustainable and inclusive city, the practical outcomes of hosting the Games did not adequately address the fundamental urban challenges and the needs of Rio's residents. Despite promising sustainable development, there was a significant disconnection between promises and achievements [33,93]. As emphasized by Wade [91], the Rio Games were largely marked by scandals and left the city starkly divided between rich and poor, much as it was with only a few cosmetic changes.…”
Section: Operational Insights From the Rio Gamesmentioning
confidence: 99%
“…Sustainability is a primary objective of the Olympics overseen by the International Olympic Committee (IOC). Given the extensive scale and impacts of the Olympics, the IOC advocates for sustainability initiatives to enhance positive outcomes and minimize negative consequences associated with hosting such mega-events [33]. The IOC has embraced the concept that investments made by host cities in Olympic infrastructure should be regarded as integral components of a broader urban agenda.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars are dedicated to studying the tangible/intangible impact of the Olympics, or to analyzing the performance of the Olympics from three dimensions (Weiler & Mohan, 2010), namely ecology (Cao et al, 2013; De Conto & Pereira, 2014), society (Baumann et al, 2010; Minnaert, 2012; Miyoshi & Sasaki, 2016), and economy (Porter & Fletcher, 2008; Preuss, 2004; Scandizzo & Pierleoni, 2018). Some scholars have built up models to evaluate and compare the sustainability of the Olympic Games (Müller et al, 2021; Trendafilova et al, 2022). Müller et al (2021) assessed the sustainability of all Olympic events between 1992 and 2020 and the result showed that the sustainability of most of the Games was weak.…”
Section: Introductionmentioning
confidence: 99%